Folk music - Kirgiss, Crystal (North Mankato, Minn. : Smart Apple Media, 2001)
Defines folk music and traces its history and development in the United States, including its resurgence in popularity starting in the 1940s.
Includes index.
Keywords: Popular music; Folk music